2021
DOI: 10.2147/jmdh.s327568
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Appendicitis During the COVID-19 Pandemic is Significantly Different: A Retrospective Single UK Hospital Study

Abstract: Introduction:The COVID-19 pandemic has led to a change in the delivery of acute and emergency surgical services. With emphasis on reducing unnecessary operative intervention and performing more CT scans, there has been a shift in managing acute appendicitis conservatively. We evaluate the impact of this shift on the management of acute appendicitis. Methods: A single UK centre retrospective study evaluating patients with suspected acute appendicitis pre-COVID-19 rota (18 March 2020) and post-COVID rota impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 16 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…On the other hand, prolonged preoperative intervals were reported during the pre-pandemic period in two studies[ 15 , 18 ]. There were two studies that concluded that the diagnostic process was prolonged during the COVID-19 period[ 10 , 13 ]. One important point that should be emphasized regarding the reported intervals in studies is that all were self-reported intervals.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, prolonged preoperative intervals were reported during the pre-pandemic period in two studies[ 15 , 18 ]. There were two studies that concluded that the diagnostic process was prolonged during the COVID-19 period[ 10 , 13 ]. One important point that should be emphasized regarding the reported intervals in studies is that all were self-reported intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Antakia et al [ 18 ] reported that during the COVID-19 pandemic, they have used CT 2.6 times more frequently (OR: 2.6; P = 0.008), but the use of US was reduced by 1.6 fold (OR: 1.6; P = 0.227). Khan et al [ 13 ] showed that US was performed less frequently, and use of CT for the diagnosis of AAp increased during the pandemic period (OR: 3.7; P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations